Magnetization dynamics and frustration in the multiferroic double perovskite Lu2MnCoO6 - Zapf, V; Ueland, B; Laver, M; Lonsky, M; Pohlit, M; Müller, J; Lancaster, T; Möller, J; Blundell, S; Singleton, J; Mira, J; Yañez-Vilar, S; et al. (American Physicals Society, 2016)
We investigate the magnetic ordering and the magnetization dynamics (from kHz to THz time scales) of the double perovskite Lu2MnCoO6 using elastic neutron diffraction, muon spin relaxation, and micro-Hall magnetization measurements. This compound is known to be a type II multiferroic with the interesting feature that a ferromagneticlike magnetization hysteresis loop couples to an equally hysteretic electric polarization in the bulk of the material despite a zero-field magnetic ordering of the type ↑↑↓↓ along Co-Mn spin chains. Here we explore the unusual dynamics of this compound and find extremely strong fluctuations, consistent with the axial next-nearest-neighbor Ising (ANNNI) model for frustrated spin chains. We identify three temperature scales in Lu2MnCoO6 corresponding to the onset of highly fluctuating long-range order below TN = 50 ± 3 K identified from neutron scattering, the onset of magnetic and electric hysteresis, with change in kHz magnetic and electric dynamics below a 30 K temperature scale, and partial freezing of ∼MHz spin fluctuations in the muon spin relaxation data below 12 ± 3 K. Our results provide a framework for understanding the multiferroic behavior of this compound and its hysteresis and dynamics.